Dangerous waters [videorecording (DVD)] - Barr, John; Jackson, Mark; Rush, Odeya, 1997-; Dane, Eric, 1972-; Burrows, Saffron; Liotta, Ray (Brainstorm Media, 2024)
Nineteen-year-old Rose lives a tough, small-town life in Florida with her single mother Alma. Their luck seems to take a turn when Alma's new businessman boyfriend, Derek, whisks them away on a sailing adventure to Bermuda. While at sea, Derek's "business" is revealed to be less than legitimate when their boat is attacked by savage villains, set on fire, and Alma is viciously killed. Distraught and persecuted by Derek and The Captain, Rose unearths a primal instinct of survival and a terrifying need for vengeance. She will not yield until those responsible for her mother's murder are dead.